Nursing Experimental Research: Analysis of the Effectiveness of Spiritual Support on Pre-Operative Patient Anxiety in the Central Surgical Installation - Jainurakhma, Janes; Arini, Ida; Hardiyanto, Hardiyanto (Akademi Kesehatan Rustida, 2025)
Pre-operative anxiety is often experienced by patients due to the uncertainty of the procedure, fear of pain, and concern about the outcome of the surgery. Although anxiety management has become a nursing concern, many patients still experience high anxiety, which can affect their physical, psychological and postoperative recovery. The study aimed to analyze the effect of spiritual support (prayer guidance) on anxiety in pre-operative patients at the Central Surgical Installation (IBS) of the Kanjuruhan Regional General Hospital (RSUD), Malang Regency. The research is designed with pre experimental, one group pre-test and post-test design. Population All pre-operative patients at IBS Kanjuruhan Hospital. The sample was determined by purposive sampling technique, with a sample size of 80 respondents. The instrument used was the Zung Self-Rating Anxiety Scale (ZSAS) questionnaire. Data analysis with the Wilcoxon test. The results showed that most of the pre- operative patients experienced moderate anxiety (52.5%) with a median score of 64. After the spiritual support intervention (prayer guidance), the majority of respondents experienced a decrease in anxiety to mild (52.5%) with a median score of 47. The results of the Wilcoxon test obtained a p < value of 0.001, there was a significant influence of prayer guidance on anxiety where 76 out of 80 respondents experienced a decrease in anxiety levels. Pre-operative patients need spiritual support, one of which is prayer guidance, this helps relaxation, strengthens patient confidence, and courage through spiritual connections so that it can reduce anxiety levels in pre-operative patients.